To Gain A Foothold in the Luxury EV Market for Chinese New Car-making Forces Brands: Resonate with Consumers through Branding First. Issue 1 (June 2021) - Li, Li; Li, Tianfeng; Cui, Jitong; Gu, Yingxiao; Zhang, Jing
Abstract: This article used a mixed methods to study the competitive disadvantages of Chinese new car-making forces brands compared with well-known foreign brands. First, based on the consumer resonance theory, the relationship between luxury EV consumers' self-presentation needs and purchase intention was explained. On this basis, the contents of luxury EV consumers' self-presentation needs and the product attributes they concerned were investigated through a qualitative study, and then the model to describe the relationships of luxury EV consumers' purchasing intention, self-presentation needs and the product attributes was built. Finally, a quantitative research was performed to verify the reasonability. It was found that Chinese consumers buy luxury EV to express their self-presentation needs including business success, quality-pursuit and pragmatism. A luxury EV with a higher level of brand awareness and technological innovation, a beautiful appearance, a safe design and cost-effectiveness can meet their self-presentation needs. There is a big gap between the brand awareness, technology innovation and appearance of Chinese new car-making forces brands and the well-known foreign brands. In the future, Chinese new car-making forces should highlight the expression of drivers' characteristics of business success, quality-pursuit and pragmatism when branding, as well as attach great importance to traditional publicity channels.